Analisis Peningkatan Angka FDI Inflows Arab Saudi Di Tengah Keterlibatan Pemerintah Arab Saudi DALAM Pelanggaran HAM - Ramadhanty, Arva Salsa; Parameswari, A.A Ayu Intan; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2020)
This research objective is to explain the increment of Saudi Arabia’s FDI inflows in 2017-2019 amidst the involvement in human rights abuse. As it is known, Saudi Arabia has bad reputations on human rights. Saudi involvement on human rights abuse in 2017-2018 has provoked the international community and threaten the reputation of Saudi on foreign investment. But these do not make the Saudi’s FDI inflows showed a significant decrease. This research uses explanative qualitative as the research method. The framework of this research is using Foreign Policy and Human rights and also The Bottleneck Effect and The Social Risk on FDI. The research showed an answer that Saudi’s involvement in human rights abuse does not affect the FDI inflows because Saudi has been working on planning to attract the foreign investment with their foreign policy and KSA Vision 2030.   Keywords : FDI, Human Rights, KSA Vision 2030, Saudi Arabia